2021
DOI: 10.28945/4709
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Factors that Affect the Use of Virtual Classrooms: A Modification of the UTAUT Model

Abstract: Aim/Purpose: The aim of this study was to examine the factors that may influence the use of virtual classrooms. Background: The coronavirus (COVID-19) pandemic has affected and interrupted several aspects of our lives, including education. Most educational institutes and universities have changed their teaching mode from being face-to-face or fixable learning to ‘emergency remote education’. As a result, virtual classrooms were utilised in most of these universities to keep the continuity of teaching and deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…For SI, this study supports previous studies by ( Raman et al, 2014 ; Hsu, 2012 ; Alshehri et al, 2019 ), as they also found SI significant for LMSs uses and contradicts studies by ( Sultana, 2020 ; Alshammari, 2021 ; Zwain, 2019 ; Bouznif, 2018 ). The contradicts in the results indicate that the social impact differs from one context to another.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…For SI, this study supports previous studies by ( Raman et al, 2014 ; Hsu, 2012 ; Alshehri et al, 2019 ), as they also found SI significant for LMSs uses and contradicts studies by ( Sultana, 2020 ; Alshammari, 2021 ; Zwain, 2019 ; Bouznif, 2018 ). The contradicts in the results indicate that the social impact differs from one context to another.…”
Section: Discussionsupporting
confidence: 64%
“…( Venkatesh et al, 2003 ) argued and confirmed that BI has a significant influence on the actual use of technology. Furthermore, previous studies have found a positive effect of BI on the actual use of technology ( Al-Adwan et al, 2018 ; Abu-Al-Aish and Love, 2013 ; Alshammari, 2021 ). Regarding LMS ( Hsu, 2012 ; Raza et al, 2021 ; Zwain, 2019 ; Alshehri et al, 2019 ; Sultana, 2020 ), they have found a positive effect of BI on the actual use of LMS.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…One variable that has been cited consistently as a possible impediment to the efficacy of such initiatives is that of end-user acceptance. For instance, user acceptance studies on online meeting platforms like Zoom and Microsoft has been on the rise (Alfadda & Mahdi, 2021;Alshammari, 2021;Bui et al, 2020;Mpungose, 2021;Olugbade & Olurinola, 2021;Pal & Vanijja, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Chen & Roldan, 2021;Dunaway & Kumi, 2021;Johnson et al, 2020;Prentice et al, 2020). A few studies have been seen to develop research models to investigate student learning, but most of them applied existing models related to information systems acceptance and adoption (Alshammari, 2021;Rizun & Strzelecki, 2020;Shahzad et al, 2021;Tiwari, 2020). To the best of the authors' knowledge, the current study is the first to leverage the theoretical lenses of both switching costs and various types of qualities to assess student learning in this new context, and further examine gender differences based on it.…”
Section: Introductionmentioning
confidence: 99%